Seismic behavior of torsional asymmetric buildings with soil structure-Analysis - Pant, Apeksha; Mishra, Gaurav (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2017)
In this work, many existing buildings contain irregularity due to functional and aesthetic requirements. However, past earthquake records show the poor seismic performance of these structures. This study also revealed that for the structure having spring support, the time period is almost same for symmetric and plan asymmetric buildings but is decreasing by 45% for vertical asymmetric building. Also, the displacement is decreasing by 10%, 9.7% and 17.3% for L type, T type and A type asymmetric building respectively.